(untitled) (E Global Congress, 2024)
In recent years, various obstacles to business and investments have been removed in Uzbekistan, and an open and strict policy is being implemented. Today, our country has established close cooperation with major international financial institutions and organizations such as the World Bank, the Asian Development Bank, the Islamic Development Bank, the European Bank for Reconstruction and Development, and the Asian Infrastructure Investment Bank.